2022
DOI: 10.1002/ueg2.12286
|View full text |Cite
|
Sign up to set email alerts
|

New concepts in the treatment of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the third most common cause of cancer-related death and occurs mainly in the context of chronic liver disease at cirrhosis stage.The Barcelona Clinic Liver Cancer classification, first established in 1999, is the most commonly used staging system for HCC in Western countries that link tumor burden, liver function and performance status with prognosis and therapeutic management. Since the first publication of this classification, it has been implemented in several clinical guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 87 publications
(152 reference statements)
0
41
0
Order By: Relevance
“…The incidence of hepatocellular carcinoma (HCC), the third most prevalent cancer-related cause of death worldwide, is rising ( 38 ). Infection with the hepatitis C and B viruses ( 39 ), alpha-1-antitrypsin deficiency ( 40 ), heavy alcoholism ( 41 ) cirrhosis ( 42 ), hemochromatosis ( 43 ), are risk factors associated with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of hepatocellular carcinoma (HCC), the third most prevalent cancer-related cause of death worldwide, is rising ( 38 ). Infection with the hepatitis C and B viruses ( 39 ), alpha-1-antitrypsin deficiency ( 40 ), heavy alcoholism ( 41 ) cirrhosis ( 42 ), hemochromatosis ( 43 ), are risk factors associated with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…This system combines liver biochemical parameters, radiological imaging and performance status with treatment guidelines [Child-Pugh, Model for End-Stage Liver Disease (MELD), Albumin-Bilirubin (ALBI) score, Eastern Cooperative Oncology Group (ECOG) Performance Scale] [ 14 , 15 ]. The algorithm has recently undergone an update, introducing the concept of treatment stage migration (TSM) [ 16 ]. TSM requires valuable input from the multidisciplinary team (MDT) as it seeks to consider non-hepatic factors, such as age, donor availability, and co-morbidities, in order to ‘assign’ patients to a more advanced treatment stage than initially recommended by BCLC staging guidelines [ 4 ].…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…IO combination therapy has been introduced and practice changing in first-line therapy of HCC in BCLC stage C. The combination of atezolizumab (PD-L1-inhibitor) and bevacizumab (VEGF-inhibitor) showed encouraging antitumor activity and safety in a phase 1b trial involving patients with unresectable hepatocellular carcinoma [ 238 ]. Based on the results of the IMbrave-150 trial the combination of bevacizumab and atezolizumab became a new standard of care in first-line treatment of HCC in BCLC stage C [ 13 , 14 ]. In this randomized phase III clinical trial, the combination of atezolizumab and bevacizumab has demonstrated superiority compared to sorafenib.…”
Section: Systemic Therapy For Hcc Bclc Cmentioning
confidence: 99%
“…Updated classifications and treatment options are illustrated as red boxes and arrows. This updated BCLC system further contains new workflows during radiological progression within between the stages (BCLCp-B, BCLCp-C1, BCLCp-C2) [ 13 , 14 ].…”
Section: Figurementioning
confidence: 99%